Systematics of eastern Nearctic Leuctra moha Ricker, 1952 with notes on L. hicksi Harrison & Stark, 2010 (Plecoptera: Leuctridae) - Grubbs, Scott A.; Metzger, Madeline L.; Wei, Summer (Zootaxa, 2020)
The female of eastern Nearctic Leuctra moha Ricker, 1952 is formally described for the first time. The identity of the female was confirmed with tree- and genetic distance-based phylogenetic methods. An emended description is also provided for the male. Digital images for both sexes are provided with scanning electronic and standard light microscopy. The female once tentatively associated with the male of L. moha is illustrated using standard light microscopy and refers to L. hicksi Harrison & Stark, 2010. An updated distribution map is provided for both species.